TINGKAT PENGETAHUAN DAN SIKAP SISWA SMP TENTANG KESEHATAN REPRODUKSI REMAJA BERDASARKAN KEIKUTSERTAAN PADA PROGRAM PUSAT INFORMASI DAN KONSELING-REMAJA (PIK-R) - Juliana, Ima; Rahmayanti, Devi; Damayanti, Emmelia Astika F. (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
Adolescence is a period of growth and development in all aspects. The most prominent problemrelated to teenage growth is the problem of reproductive health. To solve the problem, thegovernment made a programme called PIK-R which is a service and counseling related to theKRR managed from, by, and for adolescents. This study aims to determine differences in the levelof knowledge and attitude of junior high school students about adolescent reproductive healthbased on participation in PIK-R programme. This research used comparative research designwith cross sectional approach. Sample counted 46 respondents. The sampling technique wasaccidental sampling. The instruments used was questionnaire of respondent characteristics,questionnaire knowledge about reproductive health, and questionnaire about reproductive healthattitude. The results showed that there was no difference in the level of knowledge and attitude ofjunior high school students about adolescent reproductive health based on participation in PIK-Rprogramme with p-value of knowledge 0,372 and p-value of attitude 0,104.